KERAPATAN DAN PRODUKSI SERASAH TUMBUHAN RIPARIAN DOMINAN PERAIRAN SUNGAI SIAK DI DESA BELADING KECAMATAN SABAK AUH KABUPATEN SIAK PROVINSI RIAU - Nur El Fajri; Eni Sumiarsih; Ridho Ika Dewi Afdi Yeni (Berkala Perikanan Terubuk, 2009)
The aim of this study is to understand the density and litterfall productionof riparian plant dominant DAS Siak in the Belading Village, Sabak Auh Sub-Regency, Siak Regency, Riau. This reseach was conducted on Mei to Juni 2009.Method used in, this research was a purposive sampling method. There were onestations, and there is 18 sampling drop, sampling take after two week, 1 monthand 2 month. Sample was analyzed in Aquatic Ecology Laboratory of Fisheriesand Marine Science Faculty, Riau Univesity.Results shown that the riparian plant obtained consist of six familiy, therewere Malvaceae (1 species), Lauraceae (1 species), Apocynaceae (1 species),Lecythidaceae ( 1 species), Euphorbiaceae (1 species) and Caesalpiniaceae (1species). The highest importance value of tree level is Hisbiscus tiliceus (138,40), with density 0,02 trees/ha. The riparian plant dominant were Hisbiscustiliceus (0,25). Litterfall production of riparian plant dominant DAS Siak isHisbiscus tiliceus (203,1gr/m2/month) dan Beilschmiedia roxburghiana (133,2gr/m2/month).